Operator Overloading as a DSL Parsing Mechanism - Simões, Alberto (2021)
This chapter describes an approach for the implementation of embedded domainspecific languages by using operator overloads and the creation of abstract syntax trees in run-time. Using the host language parser, an AST is created stating the structure of the DSL expression that is later analyzed, simplified, and optimized before the evaluation step. For the illustration of this process, the chapter proposes a domain-specific language for a basic linear algebra system dealing with matrices algebra and its optimization.